Analisis Perbandingan Fraud Pentagon dengan Beneish Ratio dalam Pendeteksian Fraudulent Financial Reporting dengan Opini Audit sebagai Variabel Moderating - Aris Sanulika; Wahyu Nurul Hidayati (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2021)
ABSTRACTFraudulent Financial Reporting is a deliberate attempt by a company to deceive and mislead users of financial statements, especially investors and creditors, by presenting and manipulating the material value of financial statements. This study aims to determine how the auditor's opinion can moderate the comparative analysis of the pentagon fraud with the beneish ratio in the detection of fraudulent financial reporting. The type of data used in this study is comparative quantitative data. The data source in this study is secondary data. The population in this study are banking companies listed on the IDX. With a sample of 16 publicly traded companies engaged in financial and banking institutions and were listed on the Indonesia Stock Exchange in 2014-2017. The results of this study indicate that of 64 samples there were 12.5% which indicated that the financial statements had been manipulated. Auditor opinions can increase the influence of Financial Stability, external auditor quality, change in auditor, change of directors, days sales in receivables index, sales gross margin Index, Asset Quality Index, growth index, depreciation index, sales, and general administration expenses index, leverage index, total accrual to fraudulent financial reporting. Beneish Ratio affects Fraudulent Financial Reporting while Fraud Pentagon does not affect Fraudulent Financial Reporting